Optimized method for multi-axial fatigue testing of wind turbine blades. (1st February 2021) - Castro, Oscar; Belloni, Federico; Stolpe, Mathias; Yeniceli, Süleyman Cem; Berring, Peter; Branner, Kim
Abstract: An optimized method for testing wind turbine blades under fatigue is suggested. With this method, material-based damage targets along the blade are reached by applying an optimal combination of different uni- and multi-axial test blocks. The combination of test blocks is found using continuous linear optimization. Aeroelastic simulations are carried out to estimate both target and test strain-based damage in the blade. By applying the proposed method to a commercial wind turbine blade, the presented analysis illustrates that improved fatigue tests compared to current standard fatigue tests can be obtained in terms of both accuracy and total test time.